Resonant Absorption of Electromagnetic Radiation in Matrix Disperse Systems with Metallic Inclusions - Grechko, L. G.; Blank, A. Ya.; Panchenko, O. A.; Pinchuk, A. A. (Видавничий дім «Академперіодика», 2012)
Resonant Absorption of Electromagnetic Radiation in Matrix Disperse Systems with Metallic Inclusions